THE TRUST FACTOR: A COMPREHENSIVE REVIEW OF ANTECEDENTS AND THEIR ROLE IN SHAPING ONLINE PURCHASE INTENTIONS - Sulistyowati, Tussi; Husda, Nur Elfi (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: This study investigates trust's impact on consumer buying decisions and trust levels within e-commerce, shedding light on trust antecedents and their role in shaping purchase intentions. Methods: This qualitative study, conducted on September 21, 2023, employed a systematic literature review approach. Using the Scopus database in conjunction with Harzing's Publish or Perish 8 tool, the study focused on 23 articles concerning trust and online purchases. These articles were meticulously selected from a pool of 775 papers published between 2019 and 2023. Results: E-commerce trust research reveals recurring themes like reputation, risk, information quality, and utility, along with social support, subjective norms, fulfillment, trustworthiness, and vendor reliability. Trust plays a central role by mitigating risk, mediating relationships, and predicting purchase intent, influenced by content quality and social presence. These findings emphasize trust's significance in shaping online purchase intentions. Conclusion and suggestion: Understanding trust's complexity and its various antecedents is vital for businesses to tailor effective strategies, influencing online sales and consumer decisions in e-commerce. This research enhances trust comprehension in e-commerce, especially in emerging markets, by identifying key antecedents and providing a comprehensive framework. However, limitations include potential exclusions based on title format criteria and reliance on specific titles from 2019-2023. Future research should incorporate current publications and explore broader dynamics of consumer behavior in e-commerce.